Work programme 2009 - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"This work programme outlines how Cedefop will support development of European VET policy in 2009. It is divided into: (a) a narrative which reviews the policy background and then outlines how Cedefop will take forward each of its four priorities in 2009: informing European VET policies; interpreting European trends in and challenges for skills, competences and learning; assessing VET's benefits; raising the profile of VET; (b) detailed activity and project fiches. They present Cedefop's work in a logical framework, showing the expected impact of each activity and the output of each related project. An activity may include several projects and it should be noted that not all projects in a particular activity serve the same priority; (c) an activity-based budget (ABB) that shows the human and financial resources allocated to each activity." (Hrsg., BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; CEDEFOP; Programm; Berufsbildung; Förderung; Internationale Zusammenarbeit; Berufsbildungspolitik; Europäische Union